2020
DOI: 10.1111/1365-2745.13373
|View full text |Cite
|
Sign up to set email alerts
|

Responses of plant–pathogen interactions to precipitation: Implications for tropical tree richness in a changing world

Abstract: Tropical tree‐species richness is positively correlated with annual precipitation, but the mechanisms remain unclear. Phytopathogens promote tree‐species coexistence by disproportionately afflicting seedlings of locally abundant species, generating a rare species advantage. We consider whether increased plant–pathogen interactions in humid conditions favourable for phytopathogens could drive the precipitation‐richness relationship by accentuating the rare species advantage. Support for this mechanism requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 74 publications
6
29
1
Order By: Relevance
“…Seedlings experienced below average rainfall during the first month of the experiment. Drier conditions may have contributed to weaker recorded C-NDD, as increased moisture availability can enhance transmission of both above-and below-ground soil pathogens (Dorrance et al, 2003;Rossi & Caffi, 2012), with reduced precipitation limiting their ability to cause early mortality (Milici et al, 2020). Swinfield et al found increased frequency of watering resulted in significantly greater pathogen-induced seedling mortality, although even the most infrequently watered seedlings experienced substantially greater mortality than observed in our study.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Seedlings experienced below average rainfall during the first month of the experiment. Drier conditions may have contributed to weaker recorded C-NDD, as increased moisture availability can enhance transmission of both above-and below-ground soil pathogens (Dorrance et al, 2003;Rossi & Caffi, 2012), with reduced precipitation limiting their ability to cause early mortality (Milici et al, 2020). Swinfield et al found increased frequency of watering resulted in significantly greater pathogen-induced seedling mortality, although even the most infrequently watered seedlings experienced substantially greater mortality than observed in our study.…”
Section: Discussioncontrasting
confidence: 45%
“…Notwithstanding methodological issues, variation in the strength of C‐NDD likely reflects differences among species (Carson et al., 2008; Comita et al., 2014), with negative effects of conspecific density posited to more strongly influence rare rather than locally common species (Johnson et al., 2012; Mangan et al., 2010). Species life‐history strategies also affect the strength of C‐NDD (Jia et al., 2020), with trade‐offs between axes of growth and defence, at least partly, governing variation in species susceptibility of pathogens (Milici et al., 2020; Spear et al., 2015), potentially influencing seedling recruitment patterns. Shade‐tolerant species are more susceptible to fungal pathogens (Kobe & Vriesendorp, 2011; McCarthy‐Neumann & Kobe, 2008), particularly in fragmented forests (Krishnadas et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting prediction is stronger J‐C effects in more humid sites (e.g. the tropical lowlands) and sites with higher rainfall (Givnish, 1999; Milici et al ., 2020). However, for herbivore natural enemies, there were no clear latitudinal patterns (Adams and Zhang, 2009; Moles et al ., 2011; Kozlov et al ., 2015; Lim et al ., 2015; Zhang et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Soil moisture and humidity are also well known to influence pathogens, with higher pathogen activity generally associated with wetter conditions (e.g., Brenes-Arguedas et al, 2009). Changing precipitation regimes in tropical forests will likely alter plant-pathogen interactions, although the implications for tropical tree diversity are unclear (see review by Milici et al, 2020). Experimental watering resulted in higher pathogen-caused seedling mortality in a study on one tropical tree species (Swinfield et al, 2012).…”
Section: Plant-enemy Interactions and The Maintenance Of Diversity Inmentioning
confidence: 99%